농촌마을공동사업의 갈등 양상과 구조에 관한 연구 - 장우환 (한국농촌경제연구원, 2011)
The purpose of this study is to examine the aspect and characteristics of conflict among the people in the rural tourism villages shown in the course of conducting a joint project and managing a business. This study was undertaken in view of the ground theory, which includes the stage of research design, collection and analysis of information, and assessment in reliability of the study. There were 3 stages of conflict: the source, the expression and the result of this conflict. As the stage of business propulsion and the stage of business operation, the aspect of conflict in the agricultural joint business was different. The result of conflict was not only in the point of negative but also in the point of positive. Additionally, systematic management of conflict among the people in an agricultural joint business should be conducted.
Keywords: 갈등; 갈등양상; 갈등단계; 근거이론; conflict; the aspect of conflict; stages of conflict; the ground theory